2018
DOI: 10.7717/peerj.4666
|View full text |Cite
|
Sign up to set email alerts
|

Kindia (Pavetteae, Rubiaceae), a new cliff-dwelling genus with chemically profiled colleter exudate from Mt Gangan, Republic of Guinea

Abstract: A new genus Kindia (Pavetteae, Rubiaceae) is described with a single species, Kindia gangan, based on collections made in 2016 during botanical exploration of Mt Gangan, Kindia, Republic of Guinea in West Africa. The Mt Gangan area is known for its many endemic species including the only native non-neotropical Bromeliaceae Pitcairnia feliciana. Kindia is the fourth endemic vascular plant genus to be described from Guinea. Based on chloroplast sequence data, the genus is part of Clade II of tribe Pavetteae. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Scientific evaluation of plants and fungi for their medicinal or other uses can demonstrate their value, providing additional incentives to protect global natural capital. In 2019, 1,955 and 1,886 new species of plants and fungi, respectively, were reported (Cheek, 2020); some may yield compounds useful to humanity (Cheek et al., 2018). Despite these discoveries, and the success of natural product drug discovery to provide essential pharmaceuticals, the full potential of the world's biodiversity remains heavily underexplored in the search for new medicines, and in the formation of strategies for our health and well‐being.…”
Section: Resultsmentioning
confidence: 99%
“…Scientific evaluation of plants and fungi for their medicinal or other uses can demonstrate their value, providing additional incentives to protect global natural capital. In 2019, 1,955 and 1,886 new species of plants and fungi, respectively, were reported (Cheek, 2020); some may yield compounds useful to humanity (Cheek et al., 2018). Despite these discoveries, and the success of natural product drug discovery to provide essential pharmaceuticals, the full potential of the world's biodiversity remains heavily underexplored in the search for new medicines, and in the formation of strategies for our health and well‐being.…”
Section: Resultsmentioning
confidence: 99%
“…These species illustrate three points: 1) that even in tropical African countries considered well-sampled such as Sierra-Leone, numerous new species and even genera still remain to be discovered while natural habitat persists; 2) like Lebbiea , available data for most of these species shows that they are range-restricted or rare in habitat that is threatened, and so, when assessed for their conservation status, threatened with extinction; 3) the majority of these discoveries (9/16: all excepting [ 32 , 33 , 36 , 37 , 41 and 45 ]) have resulted from (high quality) EIA related studies due to mining and infrastructure projects. That EIA studies make such a major contribution to current species discovery points to the scarcity of resources from other sponsors to support botanical inventory at a time when species are probably being lost before they are discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Recent surveys in Guinea connected with the Guinea Tropical Important Plant Area programme (TIPAs) have discovered several other new species to science, all of which are threatened. Several of these are like Saxicolella futa, also rheophytes, restricted to fast flowing water habitats, such as Inversodicraea pepehabai Cheek (Cheek & Haba 2016), I. koukoutamba and I. tassing (Cheek et al 2019a), Karima scarciesii (Scott Elliot) Cheek , Lebbiea grandiflora Cheek (Cheek & Lebbie 2018;Couch et al 2019), while others are also found on the sandstone rock of the Futa such as Keetia futa (Cheek et al 2018a), Calophyllum africanum (Cheek & Luke 2016), and Kindia gangan Cheek (Cheek et al 2018b).…”
Section: Recognitionmentioning
confidence: 99%